Exposure of engineering technology students to cutting-edge technology: A multi-major senior design experience - Sahoo A.; Alexander A.; Hahn J. (My University, 2025)
Engineering Technology (ET) programs focus on the hands-on approach to engineering education. To keep pace with the rapid growth of industrial technology in the area of automation and artificial intelligence, ET programs need to introduce students to cutting-edge hands-on interdisciplinary project experiences. In this paper, such a pilot project is discussed where ET students at Oklahoma State University, Stillwater, OK have been exposed to state-of-the-art autonomous vehicle technology as an interdisciplinary senior design project. The project was introduced as a competition among teams consisting of electrical engineering technology (EET), fire protection safety engineering technology (FPSET), and mechanical engineering technology (MET) students. The objective of the project was to design a vehicle that can autonomously navigate a specified course at high speed while completing an assigned mission. The learning outcomes of the project are: (1) evaluate students for their ability to think beyond the classroom education while solving an important societal problem, (2) gain experience working in an interdisciplinary team of students with diverse backgrounds, and (3) increase the synergy among the EET, FPSET, and MET programs for a future graduate degree program in Mechatronics and Robotics. It is observed that the ET students are willing to learn and adapt to the latest open source technologies in their projects, such as OpenCV for camera vision and image processing. The paper focuses on three important aspects of the project from the perspective of ET students. First, the approaches of ET students in handling cutting-edge technology as an open-ended problem. Second, approaches of the instructors to facilitate the two-semester project along with the lessons learned. Third, both the instructor and student experiences during the project. The paper also includes sample material for project specifications, milestones, feedback, and reporting procedures along with the challenges encountered by both the students and the instructors. The paper also presents the analysis of the student outcomes accessed by the instructors, student comments, and discussion on methods to increase student motivation, participation, and project evaluation. This paper will serve as a teaching aid for the instructors who are currently teaching or plan to teach senior design in the near future. Most specifically, this will help newly joined junior faculty members in planning the senior design course and adapting some of these material and reporting procedures. © American Society for Engineering Education 2020.